Education Of The Generation Young In Context Civic Education - Sulaksono, Teki Prasetyo; Komalasari, Kokom; Bestari, Prayoga; Kurniasih, Yuli (LPPM Universitas PGRI Sumatera Barat, 2024)
Civic education for young people plays a crucial role in strengthening national character, developing social literacy, and preparing responsible citizens who can participate meaningfully in a democratic society. This study analyzes the dynamics of contemporary youth, the role of Civic Education in character formation, the function of community social spaces as authentic arenas for civic learning, and strategic efforts to reinforce civic education in the digital era. A literature review method was employed by examining nationally indexed journals published within the last five years. The findings indicate that young people face challenges such as digital disruption, social polarization, and declining face-to-face interaction. Civic Education contributes significantly to building critical awareness, social empathy, and democratic competence, especially when linked to real-life civic practices in the community. This study concludes that strengthening civic education requires synergy among schools, families, communities, and the government to cultivate knowledgeable, ethical, and socially responsible young citizens capable of navigating the complexities of national life.